HASHTAG ACTIVISM AND PUBLIC AWARENESS OF GENDER-BASED VIOLENCE IN SOUTHWEST NIGERIA: A SOCIAL MEDIA SURVEY - Oko-Epelle, Lydia (African Journal of Social and Behavioural Sciences, 2025)
Despite the growing prominence of hashtag activism as a tool for social change, empirical research examining its effectiveness in shaping public awareness and responses to gender-based violence (GBV) remains limited, particularly within the south-west Nigeria. Existing studies on digital activism have predominantly focused on Western societies, leaving a gap in understanding how social media-driven movements operate in countries like Nigeria, where cultural norms, digital access, and civic engagement differ significantly. This study addresses this gap by investigating hashtag activism awareness of gender-based violence (GBV) across three social media platforms: X (formerly Twitter), Instagram, and Facebook in Nigeria. Guided by Framing Theory and Social Movement Theory, a quantitative survey design was employed to gather empirical data on digital activism. A total of 423 respondents were selected through a multi-stage cluster sampling method from three southwestern states. Results showed that 99.2% of participants use social media, and 86% have encountered GBV-related hashtag campaigns. Although most users engage with such campaigns passively, 77% believe that social media can influence real-world change. The findings indicate that hashtag activism effectively raises awareness and frames public discourse around GBV but rarely leads to sustained offline participation. The study concludes that integrating online activism with policy advocacy and community-based initiatives may enhance the long-term impact of GBV campaigns.